A study on the rights of the illegitimate muslim children in Selangor / Farhana Yusof … [et al.] - Yusof, Farhana; Abdul Hamid, Noraini; Abdullah, Rosnizawati; Mohammad Naim, Laila Melati (Faculty of Law, 2009)
This research is conducted to determine the rights of the illegitimate children from Islamic Law perspectives and the law of other countries. This topic is chosen for the reason there will be more discussions and explanations for the future benefit. This research comprises of five chapters whereby each chapters are explaining different issues. The major discussions can be found in Chapter 3 and Chapter 4 of our research study. Chapter 3 is explaining on the issue of the illegitimate children in Islamic perspective and the status of the illegitimate children in Non- Muslim Countries. Meanwhile, in Chapter 4, this research is comparing the status and the rights of the illegitimate children in Islamic and Non- Islamic Countries. The sub-topics under this chapter consist of comparisons between the four states which are Indonesia and Egypt for the Islamic Countries and Singapore and the United States of America for the Non- Islamic Countries whereby the Islamic and the Non-Islamic Countries have different approaches in treating the illegitimate children due to different provisions as being provided in their countries. There are some findings and recommendations have been concluded in Chapter 5 based on the defect and lacuna in the law that had been found in the provision, Acts and administration regarding the rights of illegitimate children. From the legal perspectives, there is a lacuna in the law as regards to the rights of the illegitimate Muslim children because the law is currently inadequate to protect the rights of the illegitimate Muslim children.